Beyond the lesson plan: Reflective practice as a catalyst for teacher professional growth - Harsono, Arta Mulya Budi; Mahmudah, Fitri Nur; Putra, Eka Cahya Sari; Rahman, Abdul; Dewantara, Brezto Asagi; Arsyad, M. Ziyan Takhqiqi; Alfarisa, Fitri (Privietlab, 2025)
The rapid integration of artificial intelligence (AI) into education has shifted the paradigms of teaching and professional development. AI has been positioned not as a substitute for teachers but as a partner that relieves them from routine tasks, allowing greater focus on higher-order learning and reflective pedagogy. Professional standards and national regulations highlight the centrality of reflection and continuous professional growth as essential elements of teacher professionalism. Nevertheless, reflective practices backed by AI/technology lack empirical evidence, particularly for in-service teachers in primary and secondary education. To this end, this study employed an SLR design to investigate and synthesize how AI serves as a reflective partner in teachers’ PD. The review included 9,083 articles chosen from searches in the SpringerLink database and resulted in the selection of 26 articles using the PRISMA protocol. Thematically, these papers indicate AI’s contribution to enhanced reflective awareness, producing critical analyses of teaching practices, supporting reflection-informed decision making, prompting pedagogical innovation and experimentation, and promoting collaborative and continual professional learning. The results imply that AI supports teachers’ professional development and helps develop teacher noticing, providing data-driven feedback, speeding up personalization, and fostering professional learning communities. Instead of replacing teachers, AI should become a reflective partner to facilitate evidence-based pedagogy in a supportive educational policy system